Analisis Kadar Kalsium (Ca) dan Besi (Fe) dalam Kangkung Air (Ipomeae aquatica forsk) dan Kangkung Darat (Ipomeae reptan forsk) Asal Palu - Suryaningsih, Suryaningsih; Said, Irwan; Rahman, Nurdin (Jurnal Akademika Kimia, 2018)
Kangkong, or water spinach is a well-known leaf vegetable because it is delicious cheap and easily obtained. There is two types of water spinach that most consumed, water-water spinach grown in the wet and watery and land-water spinach grown in dry place or moor. Kangkong can be consumed in various type of foods, in addition, it’s also rich in vitamins, protein, carotene, amino acids, phosphorus, sitosterol and mineral materials, especially iron and calcium. The aim of the study was to determine the concentration of calcium (Ca) and iron (Fe) in water-water spinach (ipomeae aquatica forsk) and land-water spinach (ipomeae reptan forsk) from palu. The research was conducted using alkaline digestion using nitric acid with the SSA instrument. The data showed that the concentration of Ca in stems and leaves of water-kangkong was 15.375 mg/kg and 12.833 mg/kg, and land–kangkong was 74.666 mg/kg and 31.000 mg/kg, while the concentration of Fe in stems and leaves of water-water spinach was 301.166 mg/kg and 232.500 mg/kg, and land-water spinach was 458.000 mg/kg and 238.750 mg/kg.